Solving Juvenile Delinquency with Death Education Model - Azam Syukur Rahmatullah; Muhammad Azhar (International Journal of Islamic Educational Psychology, 2020)
This study discusses how to deal with juvenile delinquency in students in different ways, namely in a more spiritual way, rich in self-affection and mental enlightenment. The purpose of implementing this death education model is to bring naughty students to change for the better. The research subjects were troublesome students at SMK N 1 Mataram. In this case, 10 students followed this death education technique. This research was an applied research using the Research Development (RD) method. This study resulted in findings of the motivation for implementing death education, applying the death education model, and the death education model's advantages. There were weaknesses in the death education model. They are: (a) not all BK and PAI teachers can bring their students to a mental and spiritual phase, (b) it takes a lot of time because at least one week per phase, and there is no counseling phase (c) it cannot be applied to students below the SMK level.